Evaluation of You-Gui-Wan critical compounds inhibiting ALOX-5 and HDC gene expression in RBL-2H3 cells using a fractional factorial design. (6th April 2023) - Chen, Po-Ting; Chen, Pei-Chi; Wang, Jiu-Yao; Wang, Shulhn-Der; Lin, Li-Jen
Abstract: Ethnopharmacological relevance: The traditional Chinese medicine (TCM) You-Gui-Wan (YGW) has been used to treat asthma for hundreds of years. Aim of the study: YGW is composed of 10 types of medicinal materials. However, the immune mechanism of YGW in asthma treatment has not been elucidated. Therefore, this study investigated asthma symptoms attenuated by YGW and the underlying immune regulatory mechanism. Materials and methods: Intratracheal (i.t.) stimulation of BALB/c mice with Dermatophagoides pteronyssinus (Der p) was performed once per week (40 μL, 2.5 μg/μL). For six consecutive weeks, different doses of YGW (0.2 g/kg and 0.5 g/kg) were orally administered 30 min before stimulation with Der p. After the last stimulation, airway hyperreactivity, lung gene expression, and total immunoglobulin E (IgE) in blood were evaluated using a whole-body plethysmograph system, real-time PCR, and ELISA, respectively. In addition, DNP-IgE/DNP-BSA was added to stimulate mast cells (RBL-2H3), and YGW or various compound compositions (Trial) were added to RBL-2H3 cells for 30 min to evaluate the effects of the drug on mast cell degranulation and on gene expression. JMP 5.1 software was used to design and analyze YGW's critical compounds by which it inhibited ALOX-5 and HDC gene expression in RBL-2H3 cells. Results: YGW significantly decreased serum total IgE levels and airway hyperresponsiveness in asthmatic mice. YGW also reduced the gene expression of IL-6, TNF-α, IL-4, IL-13, and COX-2 in the lungs of asthmatic mice and RBL-2H3 cells. YGW and the compound (Trial 21) present in YGW inhibited the gene expression of ALOX-5 and HDC in RBL-2H3 cells. Conclusion: The experimental results indicate that YGW exhibits anti-airway hyperresponsiveness and specific immunomodulatory effects. In addition, YGW synergistically inhibits ALOX-5 and HDC gene expression in mast cells through a combination of 21 compounds, including luteolin, quercetin, and β-carotene. Graphical abstract: Image 1 Highlights: You-Gui-Wan extract decreased Der p - induced airway hyperresponsiveness and total serum IgE levels in a mouse model of chronic asthma. You-Gui -Wan extract inhibited the gene expression of IL-6, TNF-α, IL-4, IL-13 and COX-2 in the lungs of asthmatic mice and RBL-2H3 cells. You-Gui -Wan extract and the compounds (Trail 21) contained in You-Gui -Wan inhibited the gene expression of ALOX-5 and HDC in RBL-2H3 cells.